LA CRUZ Y EL WATESINK: SINCRETISMO TRANSCULTURAL DE LA IDIOSINCRASIA MAYA Q´ EQCHI´ EN RITUALES Y COTIDIANIDAD - David Caballero Mariscal (European Scientific Journal, ESJ, 2014)
The cross, main identification symbol of the Christianity nowadays, has taken different shapes along the story. On the other hand, it has not been always the most representative element of this religion. Still, it has monopolized the representation of the Christian religion, an authentic synecdoche of this credo and symbol of demarcation as far as another believes are concerned. At present, and as a result of difficult mechanisms of transculturality, and as an answer to conservation, different rites and pre-Columbian rites, as the watesink, show the presence of the Mayan identity. Diverse rituals conjugate facets of Mayan and Christian cultures, and they refer, in turn, to divergent significances, product of the syncretism.